Young adults’ decision making surrounding heavy drinking: A multi-staged model of planned behaviour - Northcote, Jeremy (Elsevier, 2011)
This paper examines the real life contexts in which decisions surrounding heavy drinking are made byyoung adults (that is, on occasions when five or more alcoholic drinks are consumed within a few hours).It presents a conceptual model that views such decision making as a multi-faceted and multi-stagedprocess. The mixed method study draws on purposive data gathered through direct observation ofeight social networks consisting of 81 young adults aged between 18 and 25 years in Perth, WesternAustralia, including in-depth interviews with 31 participants. Qualitative and some basic quantitativedata were gathered using participant observation and in-depth interviews undertaken over an eighteenmonth period. Participants explained their decision to engage in heavy drinking as based on a variety offactors. These elements relate to socio-cultural norms and expectancies that are best explained by thetheory of planned behaviour. A framework is proposed that characterises heavy drinking as taking placein a multi-staged manner, with young adults having: 1. A generalised orientation to the value of heavydrinking shaped by wider influences and norms; 2. A short-term orientation shaped by situationalfactors that determines drinking intentions for specific events; and 3. An evaluative orientation shapedby moderating factors. The value of qualitative studies of decision making in real life contexts is advanced to complement the mostly quantitative research that dominates research on alcohol decision making.